Circular Supply Chain: Addressing Critical Success Factors Through Multi-criteria Analysis - Tramarico, Claudemir Leif [UNESP] (Springer Nature, 2025)
The circular supply chain (CSC) is structured to sustainably circulate value by adhering closely to circular economy principles, emphasizing resource circularity through material reduction, reuse, and recycling. However, the successful implementation of CSC faces significant challenges due to inherent risks and uncertainties, necessitating robust mitigation strategies. This paper aims to comprehensively evaluate critical success factors for CSC implementation. By employing a multi-criteria analysis methodology, the study assesses CSC factors to provide valuable insights into successful implementation strategies. The integration of the Order of Preference by Similarity to Ideal Solution (TOPSIS) with the Benefits, Opportunities, Costs, and Risks (BOCR) Model enhances the evaluation process. Drawing from existing literature on circular supply chains, factors such as Political, Economic, Social, Technological, Environmental, and Legal (PESTEL) were considered as alternatives. The application of TOPSIS–BOCR revealed Environmental criteria to be of paramount importance for effective CSC implementation, highlighting its significance in driving sustainable supply chain practices.
Keywords: BOCR; Circular Supply Chain; TOPSIS